Extended Synaptotagmin Localizes to Presynaptic ER and Promotes Neurotransmission and Synaptic Growth in Drosophila. Issue 3 (7th September 2017) - Kikuma, Koto; Li, Xiling; Kim, Daniel; Sutter, David; Dickman, Dion K
Abstract: In highly polarized neurons, an extensive endoplasmic reticulum (ER) network extends to distal dendrites and axons. Several human diseases result from... The endoplasmic reticulum (ER) is an extensive organelle in neurons with important roles at synapses including the regulation of cytosolic Ca 2+, neurotransmission, lipid metabolism, and membrane trafficking. Despite intriguing evidence for these crucial functions, how the presynaptic ER influences synaptic physiology remains enigmatic. To gain insight into this question, we have generated and characterized mutations in the single extended synaptotagmin ( Esyt ) ortholog in Drosophila melanogaster . Esyts are evolutionarily conserved ER proteins with Ca 2+ -sensing domains that have recently been shown to orchestrate membrane tethering and lipid exchange between the ER and plasma membrane. We first demonstrate that Esyt localizes to presynaptic ER structures at the neuromuscular junction. Next, we show that synaptic growth, structure, and homeostatic plasticity are surprisingly unperturbed at synapses lacking Esyt expression. However, neurotransmission is reduced in Esyt mutants, consistent with a presynaptic role in promoting neurotransmitter release. Finally, neuronal overexpression of Esyt enhances synaptic growth and the sustainment of the vesicle pool during intense activity, suggesting that increased Esyt levels may modulate the membrane trafficking and/or resting Ca 2+ pathways that control synapse extension. Thus, we identify Esyt as a presynaptic ER protein that can promote neurotransmission and synaptic growth, revealing the first in vivo neuronal functions of this conserved gene family.